2008
DOI: 10.2137/1239099041838058
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth regulators to manipulate oat stands

Abstract: Plant growth regulators (PGRs) are exogenously applied chemicals that alter plant metabolism, cell division, cell enlargement, growth and development by regulating plant hormones or other biological signals. For example, some PGRs regulate stem elongation by inhibiting biosynthesis of gibberellins or through releasing ethylene. PGR effects are widely studied and reported on barley (Hordeum vulgare L.) and wheat (Triticum aestivum L.), whereas there are only a few reports addressing oat (Avena sativa L.). This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 80 publications
2
1
0
2
Order By: Relevance
“…Increases in number of grains/ panicle have been reported (Leitch & Hayes 1989). However, in agreement with the experiments reported in the present paper, Rajala (2004), in a comprehensive review of plant growth regulator effects on oats, found little evidence to suggest consistent promotional effects of chlormequat chloride, on the components of yield. Numbers of aborted primary grains were unaffected by chlormequat chloride.…”
Section: Effect Of Chlormequat Chloridesupporting
confidence: 90%
“…Increases in number of grains/ panicle have been reported (Leitch & Hayes 1989). However, in agreement with the experiments reported in the present paper, Rajala (2004), in a comprehensive review of plant growth regulator effects on oats, found little evidence to suggest consistent promotional effects of chlormequat chloride, on the components of yield. Numbers of aborted primary grains were unaffected by chlormequat chloride.…”
Section: Effect Of Chlormequat Chloridesupporting
confidence: 90%
“…Where additional grain sites were not stimulated by the application of PGRs it is probable that grain weight was reduced due to assimilate being redirected from grain sites. These results fit in with the theory suggested by Rajala (2004) who, after a wide-ranging review, concluded that varying responses in oat crops to PGR application were case specific. Although the application of PGR can exert positive effects on yield components, these effects are not as reliable or consistent as other agronomic factors.…”
Section: Discussionsupporting
confidence: 87%
“…Em cereais de inverno, o princípio ativo etil-trinexapac vem sendo utilizado em lavouras comerciais no Brasil, e seu uso tem sido indicado para a redução do crescimento das plantas em altura e para o fortalecimento dos entrenós. Embora haja escassez de informações científicas sobre os efeitos do uso de reguladores de crescimento na cultura da aveia-branca, essa prática pode ser uma alternativa para minimizar os efeitos negativos do acamamento de plantas (Rajala & Peltonen-Sainio, 2001;Rajala, 2004;Witkowicz, 2010).…”
Section: Introductionunclassified